Nature in the Eye of the Beholder: A Case Study for Cultural Humility as a Strategy to Broaden Participation in STEM - Maria N. Miriti (MDPI AG, 2019)
Science, technology, engineering, and math (STEM) disciplines suffer from chronically low participation of women and underrepresented minorities. Diversity enhancement initiatives frequently attempt to mitigate skill deficits such as math skills in an attempt to improve preparedness of these students. However, such interventions do not address cultural or social barriers that contribute to the isolation and marginalization that discourage continued participation in STEM. Science exists and is developed within social constructs.; because of this, cultural conflicts can occur pertaining to contrasting cultural belief systems between educators and students, or to socially-biased perspectives that are embedded in disciplinary values. These conflicts are implicated in the low recruitment and retention of underrepresented students in STEM. To address the relationship between culture and STEM diversity, I present a case study that examines the role of culturally-biased views of nature on the lack of diverse participation in ecology and environmental biology. I conclude by advocating the use of inclusive, culturally-sensitive teaching practices that can improve the climate for underrepresented students and increase diverse recruitment and retention in STEM.